Pengembangan Strategi Penjualan Berbasis E-Commerce untuk UMKM di Sektor Kerajinan di Kota Padang - Fathoni Ronaldi, Muhammad; Annas, Firdaus; Raihan Alfandi, M (JOVISHE : Journal of Visionary Sharia Economy, 2024)
Technological developments have brought changes to product marketing and sales, especially for Micro, Small and Medium Enterprises (MSMEs). This research aims to develop an E-Commerce based sales strategy for MSMEs in the craft sectors in Padang City, as an effort to increase competitiveness and expand market access. This research uses a qualitative approach with data collection techniques through interviews, field observations and literature studies. The results of this research show that the application of E-Commerce can bring various benefits to MSMEs, such as operational cost efficiency, increased access to a wider market and more effective marketing opportunities. However, these craft and MSMEs also face several challenges, such as limited technological knowledge so that the owners of these MSMEs still promote their products traditionally and are not widely known by the public, logistical constraints and access to digital infrastructure. As a solution, this research recommends developing a sales strategy that includes training on how to use e-commerce platforms, optimizing social media for promotions, and partnering with local logistics partners. The implementation of this strategy is expected to help craft MSMEs and incubators in Padang City utilize the potential of E-Commerce to the fullest to increase sales and support regional economic growth.